Risks of clinical trial protocol amendments according to duration of the trial - A. A. Eleskina; N. V. Pyatigorskaya; O. V. Filippova (Izdatelstvo OKI, 2023)
Background. No clinical trial could be initiated and conducted without appropriate clinical trial protocol. Any change in information relating to patients' safety and health during the trial must be recorded and approved by a form of amendment to the clinical trial protocol, which is a time-consuming and ﬁnancially expensive process for the Sponsors of these studies.Goal. To analyze the probability of releasing of clinical trials protocols amendments and to determine the most "pregnable" period for their occurrence in the course of the trials.Materials and Methods. The results of clinical trial protocols analysis are presented, which were approved by Russian Health Authorities between three years from 2017 to 2019 inclusive. In total, 20 protocols and 39 amendments were analyzed. Results. In the ﬁrst year of the study, 21 amendments were issued, representing slightly more than half (54%) of the total number of amendments. During the second year, 12 amendments were issued, (31%). For the third year of the trial, only 3 amendments (7%) were made and for the fourth - 4, which is 8% of the total.Conclusion. The largest number of protocol amendments came out at ﬁrst two years of clinical trial. Thus, they are the most "dangerous" years in the life of a clinical study in connection with the examination of developed protocol in real life. These ﬁrst two years show how carefully the protocol was designed, how it meets the requirements of regulatory authorities, criteria and recommendations of professional associations, how feasible and eﬀective the various criteria and procedures are.